Consumer behavior for ready-to-eat salad food with special reference to working people - Koli, Rachana; Prasuna, R Gyana; Watturakar, Ritu (Journal of Postharvest Technology, 2024)
In today's dynamic world, “time” has become more valuable than money. Moreover, due to an  increase in the number of working people, demand for ready-to-eat (RTE) foods has also  increased. Salad, which is the mandatory part of the daily diet, needs to be included on a daily  basis. The regular consumption of salads in the diet has beneficial effects on human health. For a  working group of people, it is difficult to carry salads at home or at their workplace on a daily basis.  This study primarily focused on consumer preferences for RTE salads, with special reference to  the working group of people in Pune. The main objective of this study was to understand the  behavior of people toward salad preference in daily diet and to understand the preference of  working professionals toward RTE salads if available readily. Researchers have focused on the  current eating habits of salads in daily diet, at work locations during mealtime hours and on  attitudes toward RTE salads. According to the research findings, working groups of people favor  © The Author(s) This is an Open Access  article licensed under a  Creative Commons  license: Attribution 4.0  RTE salads along with different salad dressings. Furthermore, consumers also believe that these  RTE salads are very convenient, time saving and easily accessible. Additionally, consumers have  stated that RTE salads can be beneficial for catering to the taste of individuals.
Keywords: Consumer behavior; convenience food,; RTE (Ready-to-Eat), salad dressings.